Function of the third party in mediation (2014)
The text offers a formal discussionof the concept of third party fromthe perspective of psychoanalysis,specifying its subjective and socialrole in mediation. It explains whythe symbolic presence of a thirdparty is necessary in the field ofsocial ties, as well as its connectionto the Lacanian concept of Nameof-the-Father. Finally, it specifiesthe role of the third party in thecivilizing of human relations, sincethese are not produced naturally.